Pengaruh Sumber Makanan yang Berbeda Terhadap Pertumbuhan Ikan Kelabau Padi (Osteochilus melanopleura) yang Dipelihara Dalam Hapa di kolam - Mardani Mardani (Fakultas Peternakan Universitas Kristen Palangka Raya, 2014)
This study aims wants to provide information about the natural food needed by the fish. The goal is to determine the effect of different food sources on growth of ‘Kelabau Padi’ fish (Osteochilus melanopleura) reared in hapa pond. These results are expected to provide valuable input for ‘Kelabau Padi’ fish farming, by looking at the growth rate, food conversion, factor conditions, mortality and water quality. Food sources used are trash fish (wet) plus Ipomoea leaves (wet) and mixed with fine bran, trash fish (wet) plus coconut cake (wet) and mixed with fine bran, and handmade artificial food containing 30 % protein.